2017
DOI: 10.1080/10826084.2017.1310246
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Behavior Among Justice Involved Male and Female Youth: Exploratory, Multi-Group Latent Class Analysis

Abstract: Results indicate a three class solution provided the optimal fit with the data for each gender group: a Lower Health Risk group, a Higher Health Risk group, and a Highest Health Risk group. Multinomial logistic regression analysis identified significant sociodemographic and depression effects among both male and female youth. Conclusions/Importance: Youth characterized by risky sexually behavior, elevated depression, and drug involvement should be the focus of integrated intervention services. This study docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Of the 46 studies that enrolled justice-involved youth (e.g., court-involved truancy, arrestees, probation, juvenile drug court, detention), a little over half of the studies (54%; n=25) included youth who were community-supervised (e.g., truancy, juvenile drug court or juvenile probation) and approximately 47% (n=21) focused on detained or incarcerated youth. With respect to study design, 22% (n=10) were intervention trials [28][29][30][31][32][33][34][35][36][37] of which 9 were randomized controlled trials (RCTs); 56% (n=26) were cross-sectional [6, and 22% (n=10) were longitudinal or prospective analysis designs [11,[63][64][65][66][67][68][69][70][71]. At time of enrollment, study participant ages ranged from 11-18 years with most studies including age range of 13-17 years and several studies extending into young adulthood (i.e., up to 30 years of age [11,27,59,61]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 46 studies that enrolled justice-involved youth (e.g., court-involved truancy, arrestees, probation, juvenile drug court, detention), a little over half of the studies (54%; n=25) included youth who were community-supervised (e.g., truancy, juvenile drug court or juvenile probation) and approximately 47% (n=21) focused on detained or incarcerated youth. With respect to study design, 22% (n=10) were intervention trials [28][29][30][31][32][33][34][35][36][37] of which 9 were randomized controlled trials (RCTs); 56% (n=26) were cross-sectional [6, and 22% (n=10) were longitudinal or prospective analysis designs [11,[63][64][65][66][67][68][69][70][71]. At time of enrollment, study participant ages ranged from 11-18 years with most studies including age range of 13-17 years and several studies extending into young adulthood (i.e., up to 30 years of age [11,27,59,61]).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that drug use (e.g., marijuana and other drugs) is associated with unprotected sex (e.g., inconsistent condom use), number of sexual partners, drug use during sexual activity and increased rates of STIs [49,51,58]. Several studies focused specifically on the effects of marijuana [6,54] or alcohol [39] alone. For example, one study found that attention-deficit-hyperactivity disorder (ADHD) was associated with sexual risk behavior for youth with conduct problems, but that cannabis use completely accounted for this association [54].…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to girls in the general population, justice-involved girls experience earlier sexual debut, higher rates of sexual activity, and higher numbers of lifetime partners (Biswas & Vaughn, 2011;Braverman, 2011;Dembo, Belenko, Childs, Greenbaum, & Wareham, 2010;Dembo et al, 2017;Gallagher, Dobrin, & Douds, 2007;Golzari, Hunt, & Anoshiravani, 2006;Hatcher, King, Nordberg, Bryant, & Woolen, 2018;Kaplan et al, 2001;Kelly, Morgan-Kidd, Champion, & Wood, 2003;Morris et al, 1995;Odgers, Robins, & Russell, 2010;Rizk & Alderman, 2012). Other risks are also prevalent in studies with justiceinvolved samples: One study reported that 19% of detained girls (n = 197) disclosed exchanging sex for money or drugs within the previous two months (Crosby et al, 2004).…”
Section: Sexual and Reproductive Health (Srh) Needs Of Justice-involvmentioning
confidence: 99%